The use of Matrix-assisted laser desorption ionization-time of flight mass spectrometry in the identification of Francisella tularensis - Karatuna, Onur; Celebi, Bekir; Can, Simge; Akyar, Isin; Kilic, Selcuk (Bosnian journal of basic medical sciences, 2016)
Francisella tularensis is the cause of the zoonotic disease tularemia and is classified among highly pathogenic bacteria (HPB) due to its low infection dose and potential for airborne transmission. In the case of HBP, there is a pressing need for rapid, accurate and reliable identification. Phenotypic identification of Francisella species is inappropriate for clinical microbiology laboratories because it is time-consuming, hazardous and subject to variable interpretation. Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) was recently evaluated as a useful tool for the rapid identification of a variety of microorganisms. In this study, we evaluated the use of MALDI-TOF MS for the rapid identification of Francisella tularensis and differentiation of its subspecies. Using national collection of Francisella isolates from the National Tularemia Reference Laboratory (Public Health Institute of Turkey, Ankara), a total of 75 clinical isolates were investigated by species and subspecies-specific polymerase chain reaction (PCR) test and MALDI-TOF MS. All isolates were originally identified as F. tularensis subsp. holarctica due to RD1 subspecies-specific PCR result. For all isolates MALDI-TOF MS provided results in concordance with subspecies-specific PCR analysis. Although PCR-based methods are effective in identifying Francisella species, they are labor-intensive and take longer periods of time to obtain the results when compared with MALDI-TOF MS. MALDI-TOF MS appeared to be a rapid, reliable and cost-effective identification technique for Francisella spp. Shorter analysis time and low cost make this an appealing new option in microbiology laboratories.